COMPARISON OF EPIDEMIOLOGICAL AND CLINICAL PARAMETERS IN PATIENTS WITH SEVERE COVID 19 TREATED WITH AND WITHOUT TOCILIZUMAB - Dimitrov, Ivica; Sazdov, Darko (Journal of Morphological Sciences; Vol 6 No 1 (2023): JMS, 2023)
Cytokine storm is an uncontrolled immune response in the immunopathogenic mechanism of COVID 19, similar to that of severe influenza. Inflammatory cytokines including: TNF-Î±, IL-6, IL-8, IL-12, are released in large amounts during of disease progression, causing potential Acute Respiratory Distress Syndrome (ARDS), Hemophagocytic Lymphohistiocytosis (HLH) and Multi-Organ Dysfunction (MOFS). Tocilizumab is an immunosuppressive drug that is used in the treatment of Rheumatoid Arthritis and Systemic Juvenile Idiopathic Arthritis in children. As a human monoclonal antibody targeting Interleukin 6 receptors (IL-6R), it interrupts its action in the cytokine storm and thereby reduces vascular permeability and increased passage of fluid and blood elements into the alveoli that would lead to severe respiratory distress (ARDS). To evaluate the effect of Tocilizumab treatment in patients with severe form of COVID-19. This retrospective study included 213 patients with a severe form of COVID-19 divided into 2 groups: Group 1 of 131 male and female patients who received Cytokine storm is an uncontrolled immune response in the immunopathogenic mechanism of COVID 19, similar to that of severe influenza. Inflammatory cytokines including: TNF-Î±, IL-6, IL-8, IL-12, are released in large amounts during of disease progression, causing potential Acute Respiratory Distress Syndrome (ARDS), Hemophagocytic Lymphohistiocytosis (HLH) and Multi-Organ Dysfunction (MOFS). Tocilizumab is an immunosuppressive drug that is used in the treatment of Rheumatoid Arthritis and Systemic Juvenile Idiopathic Arthritis in children. As a human monoclonal antibody targeting Interleukin 6 receptors (IL-6R), it interrupts its action in the cytokine storm and thereby reduces vascular permeability and increased passage of fluid and blood elements into the alveoli that would lead to severe respiratory distress (ARDS). To evaluate the effect of Tocilizumab treatment in patients with severe form of COVID-19. This retrospective study included 213 patients with a severe form of COVID-19 divided into 2 groups: Group 1 of 131 male and female patients who received Tocilizumab and Group 2 of 82 male and female patients who did not receive tocilizumab. Patients who received tocilizumab had a significantly shorter stay in the intensive care unit compared to patients who did not received tocilizumab (p=0.021). A significantly lower mortality was registered in patients who were treated with Tocilizumab . This retrospective case control study showed that treatment with Tocilizumab as a human monoclonal antibody in patients with severe form of COVID-19 can lead to shorter hospital stay and reduced mortality compared to patients who did not receive Tocilizumab. Keywords : Cytokine storm, Tocilizumab, COVID 19, Interleukin 6, ARDS. https://doi.org/10.55302/JMS2361104d